2016
DOI: 10.1071/he15096
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Sharing Stories youth theatre program: an interactive theatre and drama‐based strategy for sexual health promotion among multicultural youth

Abstract: Issue addressed: Rates of sexually transmissible infections among young people are high, and there is a need for innovative, youth-focused sexual health promotion programs. This study evaluated the effectiveness of the Sharing Stories youth theatre program, which uses interactive theatre and drama-based strategies to engage and educate multicultural youth on sexual health issues. The effectiveness of using drama-based evaluation methods is also discussed. Methods: The youth theatre program participants were 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(51 citation statements)
references
References 9 publications
2
40
0
Order By: Relevance
“…They may also be more culturally acceptable when used as community engagement tools for groups where English is not the native language or where literacy may be low. In our experience, funding agencies are increasingly open to the validity of these data and their potential for wider reach, particularly in vulnerable populations [ 43 , 44 ]. The outputs of arts-based methods (for example, photography exhibitions, theatre performances) are also powerful channels for disseminating results and have the potential to influence policy if accepted as rigorous forms of evidence [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…They may also be more culturally acceptable when used as community engagement tools for groups where English is not the native language or where literacy may be low. In our experience, funding agencies are increasingly open to the validity of these data and their potential for wider reach, particularly in vulnerable populations [ 43 , 44 ]. The outputs of arts-based methods (for example, photography exhibitions, theatre performances) are also powerful channels for disseminating results and have the potential to influence policy if accepted as rigorous forms of evidence [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The populations in the selected studies were migrants from SSA, NEA and SSA, living in high-income countries with universal health coverage. Of the 16 studies, four were conducted in Australia [46,52,53,54], three each in the Netherlands [44,47,50], Canada [55,57,58] and Italy [45,48,49] and one study in Spain [43], New Zealand [51] and Germany, respectively [56]. Of the 16 studies, two used qualitative methods [51,58].…”
Section: Resultsmentioning
confidence: 99%
“…Past research has shown that the simple provision of information was not sufficient for adolescents to learn (Boivin et al, 2018a(Boivin et al, , 2018b. Art has been used effectively in sex education (Roberts et al, 2017) and was considered a potentially engaging approach for fertility education. One reason art works is because it engages in a different way from using the standard narrative such as 'hello, I am Mary and I have fertility problems.…”
Section: Art Is Good But Not Enoughmentioning
confidence: 99%
“…The FEI want to determine how we can engage young adults to think about their future and if this involves having a family. The aim of this project is to determine the feasibility and acceptability of using art to deliver fertility education to adolescents in schools as this method can enrich learning and educational experiences (Roberts et al, 2017).…”
Section: Introductionmentioning
confidence: 99%